Transnational Plastics: An Australian Case for Global Action - Galaiduk, Ronen; Lebreton, Laurent; Techera, Erika; Reisser, Julia (Frontiers in Environmental Science, 2020)
Mitigating plastic pollution requires international cooperation because significant volumes of plastic waste are transported across jurisdictions both as waste exports and drifting ocean plastics (OP). Here we estimate which nations are (1) sources for overseas OP reaching Australian waters and (2) destinations receiving OP from Australian sources. We then provide actionable recommendations for mitigating plastic pollution in Australian waters and beyond. We estimated that the vast majority of overseas OP reaching Australia is from Indonesia, and that most of the Australian-sourced OP reaching overseas territories is entering New Zealand. Key actions for mitigating the OP issue in Australia include better governance, upgraded enforcement and increased investments to reduce fossil fuel-based plastic production and to drastically improve both domestic and international waste management infrastructure and operations.